Ethical aspects of obstetric care: expectations and experiences of patients in South East Nigeria - Iyoke CA; Ezugwu FO; Ugwu GO; Lawani OL; Onyebuchi AK (Dove Medical Press, 2013)
Chukwuemeka A Iyoke,1 Frank O Ezugwu,2 George O Ugwu,1 Osaheni L Lawani,3 Azubuike K Onyebuchi3 1Department of Obstetrics and Gynaecology, University of Nigeria Teaching Hospital, Enugu, Nigeria; 2Department of Obstetrics and Gynaecology, Enugu State University Teaching Hospital, Enugu, Nigeria; 3Department of Obstetrics and Gynaecology, Federal Medical Centre, Abakaliki, Nigeria Background: Medical ethics is not given due priority in obstetric care in many developing countries, and the extent to which patients value compliance with ethical precepts is largely unexplored. Objective: To describe the expectations and experiences of obstetric patients in South East Nigeria with respect to how medical ethics principles were adhered to during their care. Methods: This was a cross-sectional, questionnaire-based study involving parturient women followed in three tertiary hospitals in South East Nigeria. Results: A total of 1,112 women were studied. The mean age of respondents was 29.7 ± 4.1 years. Approximately 98% had at least secondary education. Ninety-six percent considered ethical aspects of care as important. On the average, over 75% of patients expected their doctors to comply with the different principles of medical ethics and specifically, more than 76% of respondents expected their doctors to comply with ethical principles related to information and consent during their antenatal and delivery care. There was a statistically significant difference between the proportions of women who expected compliance of doctors with ethical principles and those who did not (P < 0.001). Multivariate analysis showed that increasing levels of skilled occupation (odds ratio [OR] 9.35, P < 0.001), and residence in urban areas (OR 2.41, P < 0.001) increased the likelihood of patients expecting to be informed about their medical conditions and their opinions being sought. Although the self-reported experiences of patients concerning adherence to ethical principles by doctors were encouraging, experiences fell short of expectations, as the level of expectation of patients was significantly higher than the level of observed compliance for all the principles of medical ethics. Conclusion: The level of practice of medical ethics principles by doctors during obstetric care in South East Nigeria was encouraging but still fell short of the expectations of patients. It is recommended that curriculum-based training of doctors and medical students should be implemented, and hospital policy makers should do more to promote ethical aspects of care, by providing official written guidelines for adherence to medical ethical principles during obstetric care. Keywords: medical ethics, obstetric care, principles